Scholarly Interest in Forest Fires in Indonesia: A Bibliographical Review - Wulandari, Eka; Mardiatno, Djati; Susilastuti, Dewi Haryani; Maryudi, Ahmad (Forest and Society, 2022)
Forest fires in Indonesia have attracted much attention among researchers over the past few decades. This paper aims to systematically map the existing corpus of scientific knowledge on forest fires in Indonesia. The systematic maps visualize which areas of significant activity and indicate specific interests and motives. The systematic analysis is also helpful in improving the understanding of current issues, problems, and challenges. From the scientific database of Scopus, we found 209 peer-reviewed journal articles directly related to forest fires in Indonesia published between 1989 and 2021 (July). In general, the number of publications rose after major fire events, notably in 1997/1998. The El Nino Southern Oscillation (ENSO)-related big fires seem to be the primary driver of more scientific inquiries. The present review shows that although fires occurred throughout the year, they mainly occurred in the dry season, indicating the crucial role of weather even though it is not the direct cause of fire ignition. Our research shows that all types of forest functions in Indonesia have experienced fires, but approximately half of the studied fires occurred in conservation areas. More specifically, previous studies have been more dedicated to secondary forests. The studies generally pointed out that secondary forests are more prone to fires. More than a half of the existing scientific work was looking at human-induced fires, although natural hazards drove that came close. Regarding human-induced drivers, most research was dedicated to the links between fires and the use of fires in land preparation for both small-scale agricultural activities and commercial plantations. The impacts of forest fires have been the most studied topic among scholars on fires in Indonesia. More specifically, the existing research was focused on the ecological/ environmental effects dominated by studies on the impacts of air quality and biodiversity. Interestingly, the existing research rarely addressed other issues, such as local livelihoods and how they adapt to environmental changes.